(untitled) (Tribhuvan University Law Journal, 2025)
This article mainly deals with the traditional non-judicial, quasi-judicial and judicial institutions and methods that are used by the international community to resolve disputes between states. The author has started his article from introduction of international disputes and elaborates various peaceful means to settle those disputes. The author of the article points out some peaceful settlement mechanisms such as diplomatic negotiation, mediation, good offices, conciliation, arbitration and judicial process to settle international disputes. The article also summarized the procedures available within the international order for the peaceful resolution of disputes and conflicts. It explores the crucial field of using peaceful methods to settle international disputes, with a particular emphasis on the function of the International Court of Justice (ICJ). The article highlights the ICJ’s distinctive role as the main court of the UN, outlining its powers, workings, and significance in promoting world peace. It also deals with various kinds of international disputes. It highlights how crucial international law is in offering a framework for settling conflicts and preserving peace among states. Finally the author has concluded his article by showing necessity of peaceful means to settlement of international disputes.